2008
DOI: 10.1105/tpc.108.058271
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Sorting of the Solanum tuberosum Sucrose Transporter SUT1 Is Affected by Posttranslational Modification

Abstract: The plant sucrose transporter SUT1 from Solanum tuberosum revealed a dramatic redox-dependent increase in sucrose transport activity when heterologously expressed in Saccharomyces cerevisiae. Plant plasma membrane vesicles do not show any change in proton flux across the plasma membrane in the presence of redox reagents, indicating a SUT1-specific effect of redox reagents. Redox-dependent sucrose transport activity was confirmed electrophysiologically in Xenopus laevis oocytes with SUT1 from maize (Zea mays). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
109
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 83 publications
13
109
0
Order By: Relevance
“…5). Prior reports argue that SUT proteins can form homodimers and heterodimers when expressed in the same cells, and the ratio of monomers to dimers is influenced by protein abundance (Reinders et al, 2002;Krügel et al, 2008). These putative interactions could impart posttranslational control on SUT activity and lead to an inhibition of phloem loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Prior reports argue that SUT proteins can form homodimers and heterodimers when expressed in the same cells, and the ratio of monomers to dimers is influenced by protein abundance (Reinders et al, 2002;Krügel et al, 2008). These putative interactions could impart posttranslational control on SUT activity and lead to an inhibition of phloem loading.…”
Section: Discussionmentioning
confidence: 99%
“…Research presented here demonstrates that while AtSUC2p is repressed, CoYMVp is up-regulated in the presence of elevated Suc levels and thus can be used to bypass possible endogenous regulation of AtSUC2 expression at the transcriptional level. In addition to transcriptional regulation, there is evidence for posttranslational regulation of SUT activity through protein-protein interactions (Schulze et al, 2003;Krügel et al, 2008Krügel et al, , 2009Fan et al, 2009). To potentially bypass these levels of regulation, SUT genes from each of the four subfamily types (Reinders et al, 2012) were tested for the capacity to SUT OE lines perceive a P deficiency as indicated by rescue of wild-type (WT) levels of growth with P supplements and increased expression of PSI genes.…”
Section: Discussionmentioning
confidence: 99%
“…SUT genes that participate in phloem loading are transcriptionally regulated by Suc concentrations (Vaughn et al, 2002), leaf maturation (Riesmeier et al, 1993;Truernit and Sauer, 1995), diurnal cycles (Kühn et al, 1997), and possibly pressure (Smith and Milburn, 1980;Aloni et al, 1986). Posttranslational control may be mediated by protein sorting and proteinprotein interactions (Krügel et al, 2008;Liesche et al, 2010). Overexpression of SUT genes specifically in CCs to enhance loading and carbon partitioning to sink organs has been proposed as a mechanism to improve plant productivity (Ainsworth and Bush, 2011;Braun et al, 2014).…”
mentioning
confidence: 99%
“…
Based on new results, we wish to correct specific statements made in Krü gel et al (2008).The electrophysiological characterization of Zm SUT1 activation by oxidized glutathione (GSSG), as shown in Figure 4B of Krü gel et al (2008), was due to a change in pH value caused by the application of redox reagents to the medium. Here, we show that at constant pH, the application of GSSG has no affect on sucrose transport in oocytes ( Figure 9A).
…”
mentioning
confidence: 99%
“…Based on these new findings, the yeast uptake experiments reported in Figure 1 of Krü gel et al (2008) were repeated. Application of GSSG strongly affects the pH value of the broadly used 25 mM NaPO 4 buffer, depending on the GSSG concentration.…”
mentioning
confidence: 99%